Youth Emigration from the Southeast Europe : Reasons and Motivations - Ostrý, Michal; Sáenz de Viteri Vázquez, Andrea; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
The emigration of young people is an important topic in most of the South European (SEE) countries. To help understand why young people are leaving, I construct eight factors of aspirations, motivations, and values of a unique representative sample of 10 000 respondents from 10 SEE countries. Then I use the cluster analysis to group them and see if they differ in their migration intentions. I am able to differentiate 4 clusters which together have 68 % of the youth population from the region, which show a significant difference to the mean in their intention to migrate.
Vedoucí práce: Andrea Sáenz de Viteri Vázquez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses